Community Service Through Learning the Fiqh of Worship in Forming Personal Children with Karimah Morals in Cangkingan Village - Cici Cahyani (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2023)
As a Muslim, the most important worship is prayer, because prayer is the pillar of religion, of course it is customary to carry out prayer services, especially the five daily prayers, which must be started early, because at this age children are able to absorb and know the information that they can get around, to it really needs to be instilled with good religious values ​​so that one day they will have good habits and character as well. The phenomenon that occurs in today's society is generally that children are reluctant to carry out congregational prayers at the nearest mosque or musholla on the pretext of their young age, even though at a young age they need to be taught about correct worship practices according to the Prophet's syari'ah. So that this is a form of concern and contribution for our students by holding a program which has the aim of fostering the enthusiasm of children in carrying out worship, especially congregational prayers at the nearest mosque or musholla so that they can form children into personal character and have good morals.